2019
DOI: 10.3390/md17120689
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Green Technologies of Intensification for Valorization of Seafood and Their By-Products

Abstract: The activities linked to the fishing sector generate substantial quantities of by-products, which are often discarded or used as low-value ingredients in animal feed. However, these marine by-products are a prominent potential good source of bioactive compounds, with important functional properties that can be isolated or up-concentrated, giving them an added value in higher end markets, as for instance nutraceuticals and cosmetics. This valorization of fish by-products has been boosted by the increasing aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 204 publications
(142 citation statements)
references
References 94 publications
(147 reference statements)
0
141
0
1
Order By: Relevance
“…Ultrasound (UAE) can also be used to improve the extraction of lycopene. This technology increase the penetration of solvent into plant cells and favour the disruption of cell walls, which facilitates the release of contents and the contact between solvent and analyte [65,71]. The results obtained in a study carried out comparing conventional organic solvent and UAE, using in both cases hexane/acetone/ethanol, (2:1:1) as solvent, showed that UAE of lycopene required less time, lower temperature and lower solvent than conventional extraction [72].…”
Section: Conventional Techniques: Organic Solvent Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrasound (UAE) can also be used to improve the extraction of lycopene. This technology increase the penetration of solvent into plant cells and favour the disruption of cell walls, which facilitates the release of contents and the contact between solvent and analyte [65,71]. The results obtained in a study carried out comparing conventional organic solvent and UAE, using in both cases hexane/acetone/ethanol, (2:1:1) as solvent, showed that UAE of lycopene required less time, lower temperature and lower solvent than conventional extraction [72].…”
Section: Conventional Techniques: Organic Solvent Extractionmentioning
confidence: 99%
“…As commented above, in order to limit the use of large amounts of toxic organic solvents, SFE was proposed as alternative. SFE is environmentally-friendly extraction method that presented a great growth in food industries in the last decade [71]. This technique uses non-toxic organic solvents, which reduces energy use, results in more sustainable processing, and environmental pollution [79].…”
Section: Green Technique: Supercritical Fluid Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, different innovative approaches have been studied in order to valorize fish byproducts due to the environmental problem they represent; for instance, the application of green extraction technologies such as ultrasound-assisted extraction, pulsed electric fields, and supercritical fluid extraction to obtain valuable compounds from fish byproducts. These technologies allow the recovery of interesting compounds with the minimum environmental impact, reducing the use of organic solvents, which can be toxic and/or improving the extraction efficiency [5,6].…”
Section: Introductionmentioning
confidence: 99%